2000
DOI: 10.1111/j.1532-5415.2000.tb02649.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Memory Complaint in Relation to Cognitive Performance and Depression: A Longitudinal Study of a Rural Chinese Population

Abstract: SMC was associated with poorer objective memory performance even after controlling the effect of depression and demographic data, but SMC did not predict faster cognitive decline or dementia over 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 28 publications
4
71
0
7
Order By: Relevance
“…Wang et al 7 studied the relationship between SMC, depression and cognitive performance in a predominantly illiterate population and demonstrated that even when age, sex and education were controlled, there was a relationship between SMC and worse performance in tests. The authors suggested that SMC do reflect an adequate perception of memory impairment, that is to say, of maintenance of the metamemory in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 7 studied the relationship between SMC, depression and cognitive performance in a predominantly illiterate population and demonstrated that even when age, sex and education were controlled, there was a relationship between SMC and worse performance in tests. The authors suggested that SMC do reflect an adequate perception of memory impairment, that is to say, of maintenance of the metamemory in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Age has been considered a predictive variable regarding memory complaints 32,33 . Earlier studies did not, however, use the MAC-Q to assess memory complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisas longitudinais 15,16 sugerem que as queixas subjetivas de memória entre idosos sem demência não são apenas secundárias à depressão, mas refletem o status cognitivo e expressam, em parte, Endereço para correspondência: Mônica Sanches Yassuda. Gerontologia.…”
Section: Introductionunclassified